CRETACEOUS OROGENIC GRANITE BELTS, KALIMANTAN, INDONESIA - Amiruddin, Amiruddin (Pusat Survei Geologi, 2009)
Two types of Cretaceous Orogenic Granite-Belts are able to be recognized in Kalimantan, which tend to show characteristics of Cordilleran and Caledonian Granite-Types. The Cordilleran Granite-Type consists of huge granitoid batholiths known as the Schwaner, Ketapang and Singkawang batholiths. This granite type comprises tonalite and granodiorite, and minor granite sensu stricto, predominantly owning calc-alkaline to slightly alkaline composition. The granitioids are also metaluminous and slightly peraluminous which probably due to the assimilation of magma stopping. Genetically, the granite is an I-type which was formed during a subduction of oceanic crust material beneath a continental margin. Those plutons were emplaced during a longer period, ranging from 86 to 129 m.a or from Early to Late Cretaceous. The Caledonian Granite-Type comprises isolated smaller plutons of Pueh Granite, Manyukung Granite, Era Granite, Topai Granite, Nyaan Granite, Alan Granite, Kelai Granite and Sangkulirang Granite. This granite type consists of granite sensu stricto and granodiorite, having calc-alkaline and alkaline and also metaluminous and peraluminous compositions. They belong to I-type and S-type granites, suggesting that in the area, different magma sources had been generated. The Itype granite was derived from partial melting of igneous rock whereas the S-type one was derived from anatexis of sedimentary rocks of continental crust. These plutons were emplaced within a relatively short time, ranging from 74.9 to 80.6 m.a or Late Cretaceous. Keywords: Cretaceous Orogenic Belts, Cordilleran and Caledonian Granite types.